2010
DOI: 10.2298/vsp1006480t
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological evaluation of bone regeneration using human resorbable demineralized membrane

Abstract: Membrane, as a cover of bony defect, is useful and benefits bone regeneration. Bony de fects covered with RHDM show better bony healing despite the fact that bone regeneration was not fully complete for as long as six months after the RHDM implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the double layer 9 weeks membrane specimens, central intramembrane neo-ossification was clearly identified with collagen fibers embedded in the osteoid 41,42 . The efficiency of bilayer membranes in bone grafts application, in terms of bone resorption, has been analyzed in a study on rabbits 43 . Bone blocks of parietal bones were taken from one side and placed on the other, and covered with membranes.…”
Section: The Impact Of Membrane Thickness On Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the double layer 9 weeks membrane specimens, central intramembrane neo-ossification was clearly identified with collagen fibers embedded in the osteoid 41,42 . The efficiency of bilayer membranes in bone grafts application, in terms of bone resorption, has been analyzed in a study on rabbits 43 . Bone blocks of parietal bones were taken from one side and placed on the other, and covered with membranes.…”
Section: The Impact Of Membrane Thickness On Bone Regenerationmentioning
confidence: 99%
“…The resorbable human demineralized membrane (RHDM) was prepared by the combination of physical and chemical methods (demineralization of cortical bone with successive removal of lipoproteins) from human cadaver in calvarium region. These studies showed that RHDM proved a greater degree of bone regeneration compared to other membranes, especially the thicker one [43][44][45][46] .…”
Section: Collagen Membranes Of Human Originmentioning
confidence: 99%
“…How to make a suitable animal model of alveolar bone defect according to the clinical characteristics of oral bone grafting surgery is the basis and focus of studying alveolar bone repair and evaluating the osteogenic ability of bone grafting materials. Many researchers have used monkey [10], beagle [11][12], miniature pig [13][14], rabbit [15], rat [16] and other experimental animals to make bone defect models in different parts of their jaws. After the implantation of bone material, the ability to reconstruct the jaw bone was assessed by pathological methods.…”
Section: Introductionmentioning
confidence: 99%
“…Developing a suitable animal model of an alveolar bone defect according to the clinical characteristics of oral bone grafting surgery is the basis and focus of studying alveolar bone repair and evaluating the osteogenic ability of bone grafting materials. Many researchers have used monkey [10], beagle [11][12], miniature pig [13][14], rabbit [15], rat [16] and other experimental animals to develop bone defect models in different parts of the animals' jaws. After the bone material was implanted, the ability to reconstruct the jawbone was assessed using pathology methods.…”
Section: Introductionmentioning
confidence: 99%